The Strategies used by Tunas Mekar School to Teach Autistic Children in Primary School English as A Second Language - Rr, Rr. Retno Dwi Susanti (Universitas Nahdatul Ulama Surabaya, 2024)
Abstract: The objective of this study is to find autistic children use to learn English and understand how to teach English to autistic students at this elementary school. The qualitative research method was applied in this investigation. Qualitative mining yields detailed and unpredictable findings. In this instance, the principal, an English teacher, a physicist, autistic children from various backgrounds, and shadow teachers all took part in the investigation process. Tools included observations and interviews with teachers, a physicist, a shadow teacher, an English teacher, and a principal. Tunas Mekar School has the following six plans: The acronym ABA represents